1997
DOI: 10.1021/ac9612032
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Bonded Silica Stationary Phases:  Synthesis, Physicochemical Characterization, and Molecular Mechanism of Reversed-Phase HPLC Retention

Abstract: Two types of chemically bonded phases for high-performance liquid chromatography (HPLC) have been prepared:  a conventional C18 and AP (N-acylaminopropylsilica), a novel one that contains specific interaction sites localized in the hydrophobic chain. Surface properties of stationary phases, before and after chemical modification, have been characterized by several physicochemical techniques, such as porosimetry, ICP atomic emission spectroscopy, elemental analysis, solid state CP/MAS NMR, and chromatography. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 52 publications
6
52
1
2
Order By: Relevance
“…Contrarily, aminopropyl and amide groups will bind oligonucleotides because of the polar interactions i.e. hydrogen bonding or electrostatic interactions [15][16][17][18].…”
Section: Alkylamide Stationary Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, aminopropyl and amide groups will bind oligonucleotides because of the polar interactions i.e. hydrogen bonding or electrostatic interactions [15][16][17][18].…”
Section: Alkylamide Stationary Phasementioning
confidence: 99%
“…Thus, another type of stationary phase was chosen for the present study, namely alkylamide. It possesses different functional groups, which cause multipoint interactions allowing for high efficiency and an ability to distinguish between oligonucleotides [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as várias estruturas mostradas na literatura de fases estacionárias quimicamente ligadas, vêm se destacando aquelas provenientes de reagentes silanizantes contendo grupos polares inseridos no meio das cadeias alquilas, por exemplo, um reagente como XSiR 2 (CH 2 ) 3 Y(C 8 H 17 ) ou XSiR 2 (CH 2 ) 3 Y(C 18 H 37 ), sendo que Y representa grupos de amida, uréia, carbamato ou amina [42][43][44][45][46] . Estas fases exibem diferentes seletividades para analitos polares, são está-veis e reprodutíveis em fases móveis altamente aquosas e promovem picos bastante simétricos para compostos básicos 47 .…”
Section: Fases Estacionárias Quimicamente Ligadasunclassified
“…Uma vantagem da utilização destas fases, em comparação com as fases que possuem somente cadeias alquilas, está relacionada com a necessidade de menor concentração de modificador orgânico na fase móvel. Com a presença do grupo polar na fase estacionária e dependendo do soluto que se deseja separar e das condições da fase móvel, o mecanismo de retenção pode ocorrer por partição, troca-iônica ou ainda interações dipolo-dipolo 45,48 . O grande problema destas fases está relacionado com a sua baixa estabilidade em pH extremos, quando comparada com as fases que possuem somente cadeias alquilas longas.…”
Section: Fases Estacionárias Quimicamente Ligadasunclassified
“…Recently numerous modern stationary phases have been prepared and the retention mechanism has been studied in detail by using quantitative structure-retention relationships. [19][20][21][22] Despite these efforts, no universal stationary phase has been found yet to obtain reliable log P oct . Therefore, to get more insight into properties of the stationary phase, the HPLC system was simulated by a batchlike equilibrium between different compositions of aqueous methanol and octane (log P O/M-W ), and then the resultant log P O/M-W values were compared with the corresponding log k. Octane was chosen as a simple model for an alkylbonded stationary phase because our previous work 23) had shown that log k, for the compounds tested in this study, on C18 column correlated linearly with those on the corresponding C8 column (rϾ0.999) at each methanol concentration.…”
mentioning
confidence: 99%